Human Performance Analysis of Processes for Retrieving Beidou Satellite Navigation System During Breakdown - Wu, Mo; Zhang, Liang; Li, Wen-Chin; Wan, Lingyun; Lu, Ning; Zhang, Jingyu (Frontiers in Psychology, 2020)
Satellite navigation systems provide continuous, timely, and accurate signals of location, speed, and time to users all over the world. Although the running of these systems has become highly automated, the human operator is still vital for its continued operation, especially when certain equipment failures occur. In this paper, we examined 180 incidents of one particular type of equipment failure and the whole recovery process as recorded in the log files from a ground control center of the Beidou satellite navigation system. We extracted the information, including the technical description of the failure, the time when the fault occurred, the full recovery time, and the demographic information of the team members on the shift responsible for responding to the failure. We then transformed this information into the cognitive complexity of the task, time of day, shift handover period, and team skill composition. Multiple regression analysis showed that task complexity and shift handover were key predictors of recovery time. Time of day also influenced the recovery time, from midnight to 4 am, operators made longer responses. We also found that the fault handling processes could be improved if the team’s most adept member is more skillful at that role than in other teams. We discussed the theoretical and practical implications of this study.